Model Keterkaitan Market Orientation, Leadership, Organizational Innovation dan Organizational Performance pada Industri Kerajinan di Sumatera Barat - RATNI PRIMA LITA; MEUTHIA MEUTHIA; RANNY FITRIANA FAISAL (Jurnal Siasat Bisnis, 2018)
The purpose of this study is to analyze the influence of market orientation, leadership, organizational innovation and organizational performance in handycraft industry in Bukittinggi City, Pariaman City, Padang Pariaman Regency, and Pesisir Selatan Regency. This research uses quantitative methods, while the sampling technique using Purposive sampling with sample size of 86 craft companies. The criteria assigned to the respondent is the handycraft business that produce and market their own product. In this study, data were collected through the questionnaire of the owner of the handycraft industry. Data were analyzed using structural equation modeling (SEM) method with SmartPLS software. This research uses multidimensional constructions first order reflective and second order formative. Based on the data analyzed it can be concluded that leadership has a significant positive effect on business performance. This is evidenced by the two dimensions of leadership (Transactional leadership and transformational leadership) is able to explain the performance of the organization well. In addition, market orientation  have 3 dimensional (Customer orientation, resource orientation, and competitor orientation) is also able to give influence to organizational performance and organizational innovation. However, organizational innovation is not able to give a significant influence for the performance improvement of handycraft industry. It can be concluded that organizational performance in handycraft industry is influenced by market orientation conducted on consumers and competitors. And also the most important factor is how the attitude of leadership owned by the owner of handicraft industry in managing and running the business, in order to craft products in accordance with customer tastes.